Therapeutic efficacy of early photobiomodulation therapy on the zones of stasis in burns: An experimental rat model study. - Jin, Jian; Zheng, Xingfeng; He, Fang; Zhang, Yongcun; Zhou, Hao; Luo, Pengfei; Hu, Xiaoyan; Xia, Zhaofan (Wound Repair & Regeneration, 2018)
This study aimed to investigate the role of photobiomodulation therapy in preventing zones of stasis in burn wounds. We hypothesized that photobiomodulation therapy could promote tissue formation and release of nitric oxide (NO), and reduce inflammatory responses, thereby dilating local microvessels, reducing necrosis and apoptosis. Thirty rats were randomly divided into control group (CG) and laser group (LG). The zone of stasis was formed by applying a brass comb to the skin resulting in four rectangular burns separated by three unburned interspaces. The left side was laser wound (LW), while the right side was shielded wound (SW). The LW of LG was immediately subjected to photobiomodulation therapy, followed by once‐daily 30‐minutes photobiomodulation therapy sessions. Skin ultrasound and Doppler angiography analyses were used to evaluate the statuses of the zones of stasis at 1, 24, and 96 hours after injury. Harvested burn wound tissue was subjected to hematoxylin–eosin staining and HMGB1, caspase 3, and thrombomodulin immunohistochemistry, and the contents of NO and TNF‐α were measured in stasis tissue. Thrombomodulin, HMGB1, and caspase 3 immunohistochemistry revealed significantly lower positive staining rates in the LW of LG rats relative to the others at 96 hours (p < 0.05), as well as a significantly higher skin blood flow relative to the others (p < 0.05). The NO content was significantly higher in the LW of LG, compared with other wounds, at 24 and 96 hours after injury (p < 0.05). The TNF‐α level was significantly lower in the LW of LG than in other wounds at 96 hours (p < 0.05). Early, local photobiomodulation therapy can effectively ameliorate injury progression in the zone of stasis. However, these beneficial effects are limited to the directly irradiated sites.